From sixth to seventh edition of tumor, node, metastasis: Stage migration in lung cancer at a tertiary care hospital in Nepal - Acharya, Sandhya C.; Karn, A (Journal of Kathmandu Medical College, 2018)
Background: Lung cancer is the leading cause of cancer related morbidity and mortality accounting for 15.4 % of total cancer in Nepal. With revision of the Lung cancer staging system by International Association for the Study of Lung Cancerand adoption of seventh edition of staging system by American Joint Committee on Cancer in 2010, the application of seventh edition of staging system has significant impact on stage of disease which ultimately defines treatment strategyand overall prognosis.Objective: To improve stage precision by adapting new staging system, this will directly refl ect on disease treatment, survival and prognosis.Methodology: Medical records of 151 patients with lung cancer attending Oncology Department, between 2015 and 2016 were retrospectively reclassified using both sixth and seventh editions of staging system. Data were collected compared and managed using Statistical Package for Social Sciences. Ethical clearance was obtained from Institutional Review Board.Results: Stage migration was seen in 15.23 % of total cases. Seven percent of cases staged down from IIIB to IIIA. Four percent were staged up from IIIB to IV. Remaining were down staged from T4 to T3 and T3 to T2 due to sub categorization of tumor by size in seventh edition.Conclusions: There was downstage from IIIB to IIIA and upstage from IIIB to IV because of revised staging system. Thus, it is essential to have detailed radiological staging and routine pleural fluid cytology before initiation of treatment, which will further help to stage accurately and treat properly. This carries direct impact on prognosis and survival. Journal of Kathmandu Medical College,Vol. 7, No. 2, Issue 24, Apr.-Jun., 2018, Page: 55-58